The Existance of Regional People’s Representative Assembly Implementingg Its Fungtions and Roles In The Regional - Sugeng, Tedjo Asmo (International Journal of Educational Research & Social Sciences, 2021)
This research discusses functions and roles of the Regional People's Representative Assembly (DPR). Type of the research is normative model. The results of this research indicate that the existence of DPRD has not been running optimally, especially for its three functions, namely the function of legislation, budget and supervision. This is due to the lack of understanding of the human resources of DPRD members. It should be based on the principle of "good governance" doing its role as a representative institution, since DPRD positions as a counterbalancing power and exercises effective control over the regional head and all levels of regional government.